2018
DOI: 10.1002/lary.27225
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of selective neurectomy for refractory periocular synkinesis

Abstract: ObjectiveThe objective of this study was to investigate the long‐term effect and treatment stability of selective neurectomy for refractory periocular synkinesis.MethodsWe performed a retrospective review of all patients treated with highly selective neurectomy for refractory periocular synkinesis between August 2009 and August 2015. Primary outcome was time to recommencing treatment for periocular synkinesis. Palpebral fissure width was measured preoperatively, postoperatively, and at long‐term ( > 2.5 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…Although chemodenervation with botulinum toxin has been a major treatment for postparetic synkinesis, other treatments such as neurectomy 2,3) and nerve transfer 7,8) are generating renewed interest in specialists. This is because both physicians and patients generally seek definitive and permanent solutions without repetitive procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although chemodenervation with botulinum toxin has been a major treatment for postparetic synkinesis, other treatments such as neurectomy 2,3) and nerve transfer 7,8) are generating renewed interest in specialists. This is because both physicians and patients generally seek definitive and permanent solutions without repetitive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This is because both physicians and patients generally seek definitive and permanent solutions without repetitive procedures. However, selective neurectomy still requires postoperative chemodenervation in most cases [2][3][4] . Furthermore, some functional morbidity is reported after aggressive selective neurectomy 3,4) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Neurolysis has been utilized in patients with periocular synkinesis refractory to chemodenervation secondary to the formation of neutralizing antibodies. 62,63 A recent study by van Veen et al 64 investigated the long-term outcomes of selective neurectomy for refractory periocular synkinesis. The majority of patients were found to require recommencement of chemodenervation treatment within a median time of 1.2 years.…”
Section: Selective Neurolysismentioning
confidence: 99%
“…21 However, long-term follow-up demonstrated shortcomings of the original surgical approach. 22 Facial rehabilitation therapy Targeted facial neuromuscular therapy has gained widespread acceptance as a noninvasive initial treatment for NFFP. [23][24][25] A large review demonstrated targeted facial rehabilitation therapy results in quantitative improvement in facial function scores using the facial grading scale in patients with NFFP.…”
Section: Management Of Nffp Historical Treatmentsmentioning
confidence: 99%